The comparison of dented pipeline displacement calculation methods. (November 2015) - Wu, Ying; Tang, Na; Zhang, Peng
Abstract: According to dent defects on pipeline, the depth criterion cannot meet demands of oil and gas industry, so dent evaluation system based on strain is proposed. In order to obtain strain value for evaluation, the profiles of dent defects must be drawn accurately to obtain accurate displacement. The linear superposition of general solution for beam, beam on Winkler foundation, bivariate polynomial function and modified cubic spline interpolation are used respectively to simulate and calculate actual displacement of dented pipeline, and compare with results of finite element. We can know from the analysis and comparison, the result of modified cubic spline interpolation is more approximate to actual displacement of dented pipeline, which is significant for further calculating strain value of pipeline and evaluating integrity of dented pipeline. Highlights: Using four numerical methods simulate and calculate actual displacement of dented pipeline. Results of numerical methods compare with results of finite element. The modified cubicspline interpolation is the most applicable method.